Does Black Monday appear on The Indonesia Stock Exchange? - Asnawi, Said Kelana; Salim, Giovanni; Malik, Wahid Abdul (Jurnal Organisasi dan Manajemen, 2020)
Stock transactions are based on a daily transaction,where Monday begins more closed time than other days. For this reason, Monday is more volatile than other days. Findings. We find that a positive return opportunity larger (more than 60%) occurs on all trading days.This result indicates the potential for Investment in Indonesia Stock Exchange. We also found â€œBlack Mondayâ€ in sectors 1 and 9, indicate Monday Lower Return and Volume compare other days. About 77% results Monday volume lower than other days. This shows Monday trading activity has not risen. This situation does not fit the hypothesis, where after the holiday weekend, investors are eager to invest. In this case, it means that at the weekend, more negative information, so that trade transactions have not increased. Regarding the correlation between (Ï) return(o-c) and return(c-c) it is found that almost all are significantly positive except in sector 4; 5; total and LQ 45. This positive correlation indicates that not much information flow entered when the market was closed.